A Feasibility Analysis of Arabic Textbooks in Indonesia: Based on the National Education Standards Agency (BSNP) - Tri, Tri Priyatmi; Wahdah, Nurul (Journal of Arabic Language Learning and Teaching (JALLT), 2023)
The National Education Standards Agency (BSNP) is important in developing national education standards and aspects of the appropriateness of textbooks used in the learning process. However, very few studies have analyzed the suitability of textbooks based on BSNP standards. Therefore, this research aims to analyze the feasibility of Arabic textbooks based on BSNP. A qualitative design with a library research type is used to analyze textbooks. The results of this research prove that the MI class IV Arabic textbook prepared by Agus Wahyudi has met BSNP standards in terms of appropriateness of content, appropriateness of language, appropriateness of material presentation, and appropriateness of graphics with a score of 82.63% with a "very appropriate" predicate. Implications and recommendations for future research are discussed in this study.